Effects of Antiretroviral Drug Recall on Perception of Therapy Benefits and on Adherence to Antiretroviral Treatment in HIV-Infected Children - Giannattasio, Antonietta; Barbarino, Alessandro; Vecchio, Andrea L.; Bruzzese, Eugenia; Mango, Carmela; Guarino, Alfredo (Current HIV Research, 2009)
In June 2007, the European Medicines Agency announced the recall by Roche of nelfinavir from European Union markets because of contamination of tablets with ethyl mesylate. Based on this event, we investigated the effect of switching therapy because of nelfinavir recall or for other reasons on the perception of therapy benefits and adherence to treatment in HIV-infected children and their caregivers. Thirty-eight children (mean age 12.1±6.7 years) were enrolled. A 35-item questionnaire was administered to the caregivers of enrolled children. Adherence was evaluated through a 4-day recall adherence instrument. Enrolled children were divided into 3 groups: patients who were shifted because of nelfinavir recall (group A, 8 patients); patients who were shifted for other reasons (group B, 12 patients); patients who were not shifted in the last 6 months (group C, 18 patients). All caregivers considered antiretroviral therapy necessary and effective for their children. However, drug shifting generated anxiety in most of them, irrespective of the reason for shifting. At baseline, 74% patients adhered to therapy. Adherence rate was related to the type of caregivers being higher in children cared for by foster parents than in children cared for by biological parents or second-degree relatives. Adherence rates did not change significantly in groups A and B after switching. Drug-switching raises concern in caregivers of HIV-infected children and induces a negative feeling irrespective of the reason for switching. However, switching, including the shift due to nelfinavir recall, did not affect adherence rates.
Keywords: Antiretroviral therapy